Implementation of the Barton–Bandis Nonlinear Strength Criterion into Mohr–Coulomb Sliding Failure Model - Zhenwei Dai; Luqi Wang; Kaiqiang Zhang; Lin Wang; Xuecheng Gao (Advances in Materials Science and Engineering)
The stability of rocky slope is determined mainly by discontinuities. The discrete element calculation method can be used to analyze the geometric features of rock structures and to deal with the nonlinear deformation and destruction of the rock mass that may be affected by the discontinuities. In this paper, the Barton–Bandis (B-B) nonlinear strength criterion was introduced to improve the Mohr–Coulomb (M-C) slip model of joint slope. The modified model could reflect the real-time shear strength in a changing stress state. Using the numerical calculation of the shear test of the structural plane, we found that the corrected slip curve fits well with the process before the failure of the shear test. Furthermore, the modified model can track the disintegration between blocks while sliding failure of joint slope. With an increase in the number of structural planes and the complexity of the relative location of blocks, the interaction force between blocks and the sliding failure mode of the joint slope would be more complex. Changing the nonlinear parameters with the stress state of the structure plane could effectively solve this problem.